The Contribution of Hand Reaction Speed and Arm Muscle Strength to Tsuki Chudan's gyaku Punch Speed On karateka Inkanas UNM Twigs - Irmayanti, Irmayanti; Hasan, Muh Said; Hakim, Hikmad (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This study aims to determine the contribution of hand reaction speed and arm muscle strength in karate. This research belongs to the type of correlational research. The population of this study was the entire karateka of the UNM Inkanas branch. The sampling technique in this study used a purposive consecutive sampling technique so that 30 qualified male novice athletes were obtained. The data analysis technique used is a correlation analysis technique using the SPSS Version 16 system at a significant level of 95% or α0.05. Based on the results of data analysis, this study concluded that: (1) The speed of hand reaction has a significant contribution to the stroke of gyaku tsuki chudan on the karateka of the Inkanas UNM branch, a correlation value (r) of 0.682 was obtained with a probability level (0.000) < α0.05, where the speed of hand reaction contributed 46.6%; (2) arm muscle strength has a significant contribution to the gyaku tsuki chudan punch on the Inkanas UNM branch karateka, obtained a correlation value (r) of 0.604 with a probability level of (0.000) < α0.05, where arm muscle strength contributed 36.5%; (3) Hand reaction speed and arm muscle strength together have a significant contribution to the gyaku tsuki chudan punch on the UNM Inkanas branch karateka, obtained a regression value (R) of 0.727 with a probability level of (0.000) < α0.05, where the hand reaction speed and arm muscle strength together contribute 52.9%.